Interferons: the Nature, Mechanisms of Action and Clinical Use of Interferon Preparations - I.V. Dziublyk (Zaslavsky O.Yu., 2016)
The lecture deals with the use of interferons in the clinical practice. Attention is paid to the history of the discovery of interferons, mechanism of their action, efficacy of various interferon preparations.